2006
DOI: 10.1143/jpsj.75.044716
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Structural Properties of θ-type BEDT-TTF Organic Conductors under Uniaxial Strain

Abstract: In order to investigate the relationships between crystal structures and electronic properties of -type BEDT-TTF organic conductors, electrical properties of -(BEDT-TTF) 2 Ag(CN) 2 and -(BEDT-TTF) 2 CsZn(SCN) 4 and crystal structures of -(BEDT-TTF) 2 CsZn(SCN) 4 under uniaxial strain are investigated. The resistivity measurements for both salts under uniaxial strain show that the intercolumnar uniaxial strain preserves the metallic nature while the intra-columnar one induces an insulating behavior, which are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…The resemblance between the two figures suggests a relationship between the horizontal stripe and the a-axis threefold correlations. This may also be consistent with an experimental analysis under uniaxial pressure, which concluded that the value of t c is the key factor that dominates the occurrence of horizontal charge ordering [41]. A possible relation between the a-axis threefold and the horizontal stripe orderings will be mentioned in the next subsection.…”
Section: A-axis Threefold Charge Correlationsupporting
confidence: 86%
“…The resemblance between the two figures suggests a relationship between the horizontal stripe and the a-axis threefold correlations. This may also be consistent with an experimental analysis under uniaxial pressure, which concluded that the value of t c is the key factor that dominates the occurrence of horizontal charge ordering [41]. A possible relation between the a-axis threefold and the horizontal stripe orderings will be mentioned in the next subsection.…”
Section: A-axis Threefold Charge Correlationsupporting
confidence: 86%
“…35 On the other hand, according to the structural analysis of -͑ET͒CsZn͑SCN͒ 4 under uniaxial strain, the uniaxial strain along the transverse direction does not reduce the dihedral angle but reduces the lattice constant along the transverse direction. 39 This result suggests that the overlap integrals are weakly increased under the T-axis strain. Moreover, the averaged dihedral angle of the ET salt is ϳ140°, which is significantly larger than those of the -type ET compounds.…”
Section: Site-charge Distributions Under Uniaxial Strainmentioning
confidence: 92%
“…Kondo et al studied the temperature dependence of the electrical resistance under uniaxial strain. 39 The metallic behavior is preserved in the lowpressure region under the uniaxial strain along the transverse direction ͑corresponding to the a axis͒, but the electrical resistance increases above ϳ10 kbar. 39 This behavior is in agreement with that of the BETS salt under the T-axis strain.…”
Section: Site-charge Distributions Under Uniaxial Strainmentioning
confidence: 98%
See 1 more Smart Citation
“…The electronic phase diagram of this family has been composed employing the dihedral angle φ between the adjacent BEDT-TTF molecules (See Figure 9), which is related to the bandwidth [74]. The dihedral angle was subsequently linked to t c /t p to explain the phase diagram, where t c and t p are the transfer integrals along the c (stacking) direction and a ± c (diagonal) directions forming a triangular lattice [75][76][77][78]. Watanabe discussed this phase diagram using t c /t p as follows [78].…”
Section: θ-(Bedt-ttf) 2 Xmentioning
confidence: 99%